Paediatric thyroidectomy: a case report - Munjal, Manish; Munjal, Shubham; Mittal, Naveen; Arora, Vineeta; Chauhan, Swati (International Journal of Contemporary Pediatrics, 2025)
Paediatric thyroid surgery, in benign or malignant lesions nowadays is an established intervention with rare untoward sequel, short hospitalization and an excellent outcome. At most centers high volume surgeons perform thyroidectomy in patients belonging to this age group while at some, is undertaken by the below high-volume surgeons but those adept and specialized in paediatric surgery. In surgical fraternity it is emphasized that high volume paediatric and adult endocrine surgeons to be the ideal interventionists. In our opinion paediatric thyroid surgery ideally should be carried out by high-volume surgeons well conversant in knowledge of anatomy of the neck. Thereby having a favourable outcome with minimal morbidity. Subtotal thyroidectomy was undertaken in a 4-year-old female where FNAC was suggestive of benign follicular nodule. Post intervention the voice and calcium levels were normal.